2014
DOI: 10.1111/ijcs.12144
|View full text |Cite
|
Sign up to set email alerts
|

Development of functional food with the participation of the consumer. Motivators for consumption of functional products

Abstract: The purpose of the study was (1) to define the most important characteristics of functional food affecting purchasing decisions; (2) diagnose the importance of the healthful properties of functional food; (3) identify preferences for carriers (base product) and the importance of the functional components essential in the choice of functional products; and (4) get to know the motives by which consumers are guided when purchasing functional food. The data were collected through direct interview (n = 200). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 42 publications
4
50
0
8
Order By: Relevance
“…Advertising and doctors/nutritionists are the main sources of information for elderly consumers who tend to be very sceptical as they fear that there is no official control on firms' promotional statements. Consistent with other studies the presence of HC on FFs has been shown to influence consumers' perceptions of the healthiness of products (Verbeke et al, 2009;Aschemann-Witzel and Hamm, 2010;Kraus, 2015). However, elderly consumers also stated they had difficulties reading, interpreting HC, and the nutritional information on the food label.…”
Section: Discussionsupporting
confidence: 85%
“…Advertising and doctors/nutritionists are the main sources of information for elderly consumers who tend to be very sceptical as they fear that there is no official control on firms' promotional statements. Consistent with other studies the presence of HC on FFs has been shown to influence consumers' perceptions of the healthiness of products (Verbeke et al, 2009;Aschemann-Witzel and Hamm, 2010;Kraus, 2015). However, elderly consumers also stated they had difficulties reading, interpreting HC, and the nutritional information on the food label.…”
Section: Discussionsupporting
confidence: 85%
“…According to other research, food choice factors such as price, sensory appeal, and natural food content are ranked as the most important by consumers from some European countries (Markovina et al, 2015), and food naturalness in general is very relevant for consumers across countries (Román, Sánchez-Siles, & Siegrist, 2017). Furthermore, the relationship between health motivation and food choices has been repeatedly confirmed (Büyükkaragöz, Bas, Sağlam, & Cengiz, 2014;Czarnacka-Szymani & Jeżewska-Zychowicz, 2015;Kraus, 2015;Verbeke, 2005).…”
Section: Theoretical Contributionsmentioning
confidence: 95%
“…Araştırma verileri, araştırmacılar tarafından anket formu kullanılarak, üniversite öğrencileriyle yüz yüze görüşme yöntemiyle elde edilmiştir. Anket formunun, geliştirilmesi aşamasında araştırmanın temellendirilmesi ve belirlenen amaçlara ulaşabilmesi için konuyla ilgili İngilizce ve Türkçe literatür incelenmiştir (Tekün, 2015;Kraus, 2015;İpek, 2015;Demir, 2018). Literatür incelemesinden elde edilen veriler yardımıyla kavramsal yapısı ve ana çerçevesi belirlenen anket formunun üniversite öğrencileri tarafından kolayca anlaşılmasına da dikkat edilmiştir.…”
Section: Materyal Ve Metotunclassified